THE REHABILITATION FUNCTION OF SPORT IN A PSYCHOLOGICAL CONTEXT - Marzec, Arkadiusz; Woźniak, Waldemar; Sarzała, Dariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Sporting activity plays an important role in the lives of many people, while at the same time affecting their social functioning. The problem discussed in this paper refers to the psychological context of sporting activity of prisoners, who are people isolated from society and subjected to social rehabilitation. The aim of the analysis presented in this paper is to identify possible relations between sporting activity and personality traits of perpetrators of crimes participating in the rehabilitation process. This problem is socially important as some personality traits may reduce the effectiveness of rehabilitation, while others may contribute to improving the effects of such activities and, at the same time, to positive functioning in the society. An analysis of selected texts relating to the problem revealed that the prisoners who were actively involved in sports had a higher level of emotional stability and extroversion compared to those who did not engage in such activities. Emotional stability is a desirable feature. Although extroversion may be considered a positive trait, it should be approached with caution in the case of prisoners as its high level may, at least in some cases, lead to impulsive or even violent behaviour.